BEZOLD-JARISCH REFLEX: AN UPDATE ON NEUROSURGERY - Mendoza-Avendaño , María; Ramos-Villegas , Yancarlos; Galindo-Velásquez , Hather; Caamaño-Villafañe , Paola; Moscote-Salazar , Luis Rafael (Revista Argentina de Neurocirugía, 2021)
The Bezold Jarisch reflex is a cardioinhibitory reflex that plays a role in cardiovascular homeostasis. It consists of a triad given by hypotension, bradycardia, and peripheral vasodilation that can be triggered by both mechanical and chemical stimuli. The efferent counteracting mechanism is considered to inhibit the effects of sympathetic influx and, conversely, activates the effects produced by the parasympathetic system. During neurological surgery, the decrease in intracranial pressure after bone flap extraction in the craniotomy, the use of osmotic medications to decrease cerebral edema and even the position of the patient during the procedure supposes situations more prone to reflex appearance.
Keywords: Bezold Jarisch Reflex; Neurosurgery; Neurosurgical Procedures